2022
DOI: 10.1021/acscatal.2c02655
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Based Redox: Catalytic Applications and Mechanistic Aspects

Abstract: For the last few decades, coordination chemists have seen many ligands whose role pervades far beyond being a supporting ancillary. The ambiguity in their electronic structure description and challenges to the precise determination of a metal’s oxidation state, when such ligands are coordinated with a metal, have sparked intense debate. Owing to this issue, these ligands have been examined with multiple spectroscopic techniques aided by high-level theoretical calculations. Typically, difficulty in accurate ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 162 publications
0
14
0
Order By: Relevance
“…Figure 2). 14 The vacant, localized C=N * orbitals of imine-based ligands like PDIs can be exploited to access ligand-centred redox in transition metal 15 and main-group complexes. 16 For example, (PDI)Fe(L) (L = N 2 , NH 3 ) complexes contain ligand-centered triplet PDI diradical dianions antiferromagnetically coupled to ferrous iron centres, not neutral closed-shell singlet PDIs bound to Fe(0).…”
Section: Stabilization Of Reactive Intermediates In Catalysismentioning
confidence: 99%
“…Figure 2). 14 The vacant, localized C=N * orbitals of imine-based ligands like PDIs can be exploited to access ligand-centred redox in transition metal 15 and main-group complexes. 16 For example, (PDI)Fe(L) (L = N 2 , NH 3 ) complexes contain ligand-centered triplet PDI diradical dianions antiferromagnetically coupled to ferrous iron centres, not neutral closed-shell singlet PDIs bound to Fe(0).…”
Section: Stabilization Of Reactive Intermediates In Catalysismentioning
confidence: 99%
“…The BTSC‐based catalysts exhibit proton‐relay and electron reservoir characteristics, resulting in varied HER catalytic pathways (ligand‐centered, or metal‐centered) governed by metal‘s identity. Mechanistic variations of these complexes have extensively been reviewed previously [17,36] . Therefore, we review the changes in the activity of complexes when pendent amine functionalities are incorporated in the ligand structure.…”
Section: Mechanistic Variation Involving Redox Active Ligand For Hydr...mentioning
confidence: 99%
“…Lastly, the catalyst gives back hydrogen for the in situ hydrogenation of the double bond of the intermediate compound to result in the final product. Recently, it has been observed that redox non-innocent ligand-containing transition-metal complexes also can lead to borrowing hydrogen type catalysis involving the ligand-based radical pathway. Here, using a redox non-innocent azo-pyridyl ligand for the first time, we report an efficient homogeneous cobalt catalyst for alcohol dehydrogenation-triggered borrowing hydrogen C3-selective alkylation of indoles.…”
Section: Introductionmentioning
confidence: 99%